Effect of Jnana and Chin Mudras on Cardio-Pulmonary Variables among Healthy Individuals: A Single Arm Study - Ahlawat, Sachin; K, Archana; Shetty, Vanitha S; Jinaraj, Abhijna (Indian Journal of Integrative Medicine, 2025)
Mudras, specific hand, body, or eye positions, facilitate unique energy flows within the body, fostering distinct mental and conscious experiences. They enhance vitality, focus the mind, and reduce tension, and notably, calm thoughts. This study aims to evaluate the effects of Jnana mudra and Chin mudra on healthy individuals using cardiopulmonary variables. The study included 120 healthy participants, both male and female, aged 18 to 25. Pre- and post-intervention assessments were recorded, measuring systolic and diastolic blood pressure (SBP, DBP), pulse rate (PR), respiratory rate (RR), oxygen saturation (SpO2), and peak expiratory flow rate (PEFR) using a peak flow meter, cardiac monitor, and pulse oximeter. Mudras were practised for six days a week for eight weeks, followed by the post assessment. Significant decreases were observed in systolic blood pressure (p≤0.001), diastolic blood pressure (p≤0.001), respiratory rate (p≤0.001), and pulse rate (p≤0.001). There were also notable improvements in peak expiratory flow rate (p≤0.001) and SpO2 levels (p≤0.001). Gender-specific comparisons revealed significant changes in diastolic blood pressure (p≤0.001), respiratory rate (p=0.01), peak expiratory flow rate (p≤0.001), and oxygen saturation (p=0.002). These findings demonstrate the positive impact of mudras on overall cardiopulmonary health, suggesting that regular practice can enhance fitness and health outcomes.